Awareness of e-learning drawbacks among FTMSK students / Zool Fadly Arasat (Arshad) - Arasat (Arshad), Zool Fadly (Faculty of Computer and Mathematical Sciences, 2007)
E-leaming has transformed the traditional learning process into a new broader and dynamic process of learning. Although many of us might think that e-learning was only suitable for peoples who were busy especially for working peoples, it is wrong as e-learning has been adapted not just in universities but also from primary schools. The study seeks to determine level of awareness towards e-learning drawbacks among students and to identify the factors that keep the student to demand for e-learning even though the drawbacks have been known. It was also done to suggest some reduction methods in reducing the drawbacks of e-learning. The objectives have been met through the analysis. There are some limitations in this research and some recommendations are identified in order to overcome the limitations. The researcher has also learned some mistakes especially in designing the questioinnaires.